2016
DOI: 10.1186/s40645-016-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between komatiite and CO2-rich seawater at 250 and 350 °C, 500 bars: implications for hydrogen generation in the Hadean seafloor hydrothermal system

Abstract: To understand the chemical nature of hydrothermal fluids in the komatiite-hosted seafloor hydrothermal system in the Hadean, we conducted two hydrothermal serpentinization experiments involving synthetic komatiite and a CO 2 -rich acidic NaCl fluid at 250 and 350 °C, 500 bars. During the experiments, the komatiites were strongly carbonated to yield iron-rich dolomite (3-9 wt.% FeO) at 250 °C and calcite (<0.8 wt.% FeO) at 350 °C, respectively. The carbonation of komatiites suppressed H 2 generation in the flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
73
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(88 citation statements)
references
References 74 publications
12
73
3
Order By: Relevance
“…Such CO 2 -rich seawater provided seafloor hydrothermal vent environments that would sustain the emergence and early evolution of life (Takai et al 2006;Russell et al 2010Russell et al , 2014Shibuya et al 2015Shibuya et al , 2016. Furthermore, chemical exchange reactions would have had particular characteristics as the then CO 2 -rich seawater interfaced oceanic lithosphere (e.g., intense CO 2 fixation into the crust) (Nakamura and Kato 2004;Rouchon and Orberger 2008) resulting in the generation of novel high-temperature hydrothermal fluids (e.g.., alkaline, silica-rich, metal-poor fluid, and Mg-rich fluid) (Shibuya et al 2010;Ueda et al 2016). These processes would have played a significant role in controlling the chemistry of early oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Such CO 2 -rich seawater provided seafloor hydrothermal vent environments that would sustain the emergence and early evolution of life (Takai et al 2006;Russell et al 2010Russell et al , 2014Shibuya et al 2015Shibuya et al , 2016. Furthermore, chemical exchange reactions would have had particular characteristics as the then CO 2 -rich seawater interfaced oceanic lithosphere (e.g., intense CO 2 fixation into the crust) (Nakamura and Kato 2004;Rouchon and Orberger 2008) resulting in the generation of novel high-temperature hydrothermal fluids (e.g.., alkaline, silica-rich, metal-poor fluid, and Mg-rich fluid) (Shibuya et al 2010;Ueda et al 2016). These processes would have played a significant role in controlling the chemistry of early oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have revealed that high concentrations of CO 2 and thus lower pH of early Earth's oceans (Halevy and Bachan 2017) had the potential to elevate in situ pH and reduce metal concentrations in hydrothermal fluids even at high temperatures, in contrast to their modern equivalents (Shibuya et al 2013). Additionally, the experimental studies show that H 2 concentrations of hydrothermal fluids in komatiite-hosted systems would be comparable to those in modern ultramafic-hosted hydrothermal systems Ueda et al 2016). These experimental studies suggest the existence of H 2 -rich alkaline hydrothermal vents on early Earth (Macleod et al 1994).…”
Section: Earth's Hydrothermal Systems and Closed-system Hydrothermal mentioning
confidence: 99%
“…The vents would add to the general habitability of the oceans by providing nutrients and an energy source. In addition to in situ studies of terrestrial hydrothermal vent fluids and ocean floor drilling (Beaulieu et al 2015;Tivey 2011;Alt 2013), laboratory based experiments using large-scale reactors are conducted to reproduce closed-system water-rock interactions (Yoshizaki et al 2009;Shibuya et al 2013;Ueda et al 2016), which are essential for our understanding of the ocean floor on these icy moons. Efforts are also being taken to develop microfluidics devices for a more controlled setting.…”
Section: Introductionmentioning
confidence: 99%
“…Solid curves indicate solutions with 1 mol/L of Ca⊖Mg chloride. Ranges of hydrothermal fluids in this study and previous studies are plotted as individual symbols (Jones et al, 2010;Neubeck et al, 2014;McCollom et al, 2016;Ueda et al, 2016Ueda et al, , 2017 Neubeck et al, 2014;McCollom et al, 2016;Ueda et al, 2016Ueda et al, , 2017…”
mentioning
confidence: 99%
“…。カンラン石を用いた高 二酸化炭素濃度下の熱水実験は 30 ~ 320°C の幅 広い温度範囲で行われている (Jones et al, 2010;Neubeck et al, 2014;McCollom et al, 2016;Ueda et al, 2017 (Lazar et al, 2012;Hao and Li, 2015;Ueda et al, 2016 (Alt., 1995;Edmond et al, 1979;Elderfield and Schultz, 1996;Kelley et al, 2001 (Rividi et al, 2010;Rintamäki, A., 2016) and those formed in hydrothermal experiments Ueda et al, 2016Ueda et al, , 2017 (Jones et al, 2010;Neubeck et al, 2014;McCollom et al, 2016;Ueda et al, 2016Ueda et al, , 2017) . Fig. 7 Calcite⊖dolomite⊖magnesite stability fields as functions of temperature and mMg/ (mMg + mCa) value estimated from experiments at 275⊖420°C and their extrapolation to 0°C (modified after Tribble et al, 1995) .…”
mentioning
confidence: 99%